Emergent Constraints on Regional Cloud Feedbacks. Issue 10 (20th May 2021) - Lutsko, Nicholas J.; Popp, Max; Nazarian, Robert H.; Albright, Anna Lea
Abstract: Low‐cloud based emergent constraints have the potential to substantially reduce uncertainty in Earth's equilibrium climate sensitivity, but recent work has shown that previously developed constraints fail in the latest generation of climate models, suggesting that new approaches are needed. Here, we investigate the potential for emergent constraints to reduce uncertainty in regional cloud feedbacks, rather than the global‐mean cloud feedback. Strong relationships are found between the monthly and interannual variability of tropical clouds, and the tropical net cloud feedback. These relationships are combined with observations to substantially narrow the uncertainty in the tropical cloud feedback and demonstrate that the tropical cloud feedback is likely >0Wm −2 K −1 . Promising relationships are also found in the 90°–60°S and 30°–60°N regions, though these relationships are not robust across model generations and we have not identified the associated physical mechanisms. Plain Language Summary: Clouds are the largest source of uncertainty in projections of future climate change. One promising approach for constraining how clouds will change in a warmer world is "emergent constraints" in which some quantity that we can observe today, like monthly cloud variability, is related to some aspect of the climate system's response to warming, like the strength of the cloud feedback. A number of emergent constraints based on cloud variability have been proposed; however, while these worked well in the previous generation of climate models (CMIP5), they perform poorly in the newest generation of climate models (CMIP6). Here, we propose that emergent constraints on clouds can still be useful for constraining regional cloud changes, even if they cannot be used to constrain changes in global cloud cover. Using simple metrics of regional cloud variability, we demonstrate the existence of strong relationships between metrics of monthly/interannual cloud variability and the long‐term tropical cloud feedback. These relationships are robust across the model generations, and allow us to substantially narrow the uncertainty in the tropical cloud feedback. Promising relationships are also seen in several other regions, but these are less robust across the model generations. Key Points: Global low‐cloud‐based emergent constraints on equilibrium climate sensitivity fail in CMIP6 Strong relationships are found between unforced cloud variability and long‐term cloud feedbacks in several regions Regional emergent constraints suggest the tropical cloud feedback is likely positive